Character Values in Saparan Bekakak Tradition as History Learning Resource - Bahroni, Agung; Setiawan, Risky; Aria Yuliantri, Rhoma Dwi; Khoiriyah, Febriana; Fitrianti, Vionita Vara (Universitas Negeri Padang, 2024)
This research aims to analyze the character values in the Saparan Bekakak tradition to strengthen the character building of the Pancasila Student Profile through history learning in high school. This research uses a descriptive qualitative method with an ethnographic approach. Research data were obtained through observations, interviews, and literature studies. The results of the research that Saparan Bekakak is a tradition of slaughtering bekakak brides as a means of asking for safety. The character value of Saparan Bekakak reflects the character of the Pancasila Student Profile, namely (a) Believing and fearing God Almighty, (b) Global diversity, (c) Mutual cooperation, (d) Independence, (e) Critical thinking, and (f) Creative. The character values of the Saparan Bekakak tradition can be utilized as a source of learning history by integrating it with the Curriculum and Learning Outcomes, implementing conceptual history learning, making visits to the place of implementation of the Saparan Bekakak tradition, and digging up information through community leaders who are the perpetrators of the Saparan Bekakak tradition.